Experiment of Phase Unwrapping Algorithm in Interferometric Synthetic Aperture Sonar - Yun, Jun; Zou, Zhi-nong; Tang, Jin-song; Wang, Ai-qing (Eighth ACIS International Conference on Software Engineering, Artificial Intelligence, Networking, and Parallel/Distributed Computing (SNPD 2007): 30 July - 01 August 2007 / Qingdao, China, 2007)
Two-dimensional (2-D) phase unwrapping, which defined as the estimation of unambiguous phase data from a 2-D array known only modulo 2 pi radian, is a key technique in the interferometric synthetic aperture sonar (InSAS). Unfortunately there are no a set of approaches of final word on phase unwrapping especially in the real dates. Recently, an InSAS prototype is developed and the lake trials were fulfilled. The phase unwrapping algorithms in the InSAS system were analyzed and their advantages and limitation were also studied with the results of data of Lake Trail. The results we derived from the lake trail will make foundation for further research.